Colombia uses advanced model for methane emissions from livestock to inform climate change mitigation actions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Government preparers of Colombia's national greenhouse gas inventory used data, model validation and training by CCAFS-CIAT researchers to estimate national enteric methane emissions from cattle in their 2017 national communication to the UNFCCC. This advance in methods and capacity allows Colombia to estimate livestock emissions more precisely, including the effect of mitigation due to productivity improvements, which is critical for informing policy and attracting climate finance for their Nationally Appropriate Mitigation Action (NAMA) in the livestock sector.